Pediatric acute mastoiditis in the era of pneumococcal vaccination. (6th November 2017) - Tawfik, Kareem O.; Ishman, Stacey L.; Tabangin, Meredith E.; Altaye, Mekibib; Meinzen‐Derr, Jareen; Choo, Daniel I.
Abstract : Objectives/Hypothesis: The objective was to describe trends in the annual prevalence of hospitalization for pediatric acute mastoiditis since introduction of the 7‐valent pneumococcal vaccine in 2000 and the 13‐valent vaccine in 2010. Study Design: Cross‐sectional retrospective data analysis. Methods: The Kids' Inpatient Database from years 2000 to 2012 was analyzed. To determine the annual prevalence of hospitalization for acute mastoiditis, nationally weighted frequencies of hospitalization for children <21 years with acute mastoiditis diagnoses were collected. Trend analysis of hospitalization rates from 2000 to ‐2012 was performed. Results: From 2000 to 2012, there was no significant trend in hospitalization rates for acute mastoiditis overall (1.38 and 1.43 per 100, 000 persons in 2000 and 2012, respectively; P = .86) or by age group. When comparing hospitalization rates at time points 2000 and 2012, children <1 year (4.65 and 3.27 per 100, 000 persons, P = .0023) and 1 to 2 years of age (3.95 and 3.18 per 100, 000 persons, respectively; P = .0107) demonstrated declines in hospitalization over time. Between 2009 and 2012, hospitalization rates also significantly declined for children aged <1 year (4.50 to 3.27 per 100, 000 persons, P = .0056) and 1 to 2 years (4.30 to 3.18 per 100, 000 persons, P = .0002) but increased for children 5 to 9 years (1.10 to 1.81 per 100, 000 persons, P < .0001) and 10 to 20 years of age (0.41 to 0.72 per 100, 000 persons, P < .0001). Conclusions: Despite introduction of two pneumococcal vaccines, rates of hospitalization for pediatric acute mastoiditis did not decline between 2000 and 2012. Between 2009 and 2012, however, children 0 to 2 years of age showed declining hospitalization rates, possibly reflecting the protective benefit of the 13‐valent pneumococcal vaccine. Level of Evidence: 4. Laryngoscope, 128:1480–1485, 2018